IMPLEMENTASI PROSEDUR AKUNTANSI BERBASIS AKRUAL DALAM PENYUSUNAN LAPORAN KEUANGAN TERHADAP KUALITAS LAPORAN KEUANGAN - B2053151019, SUTAN HARIRI HARAHAP (Jurnal Ekonomi Daerah (JEDA), 2017)
The research entitled the procedures implementation of accounting base of accrual in the preparation of financial report toward quality of Financial Reports. Aims of this research is to find out and analyze the implementation of stages / steps / procedures of Accounting Base of Accrual in the preparation of Financial Reports produced by Regional Work Unit of urban comunities (SKPD Kelurahan) as accounting entity, Head of local government financial management office (PPKD) as informer, and Inspectorate of Ketapang Regency as government internal control (APIP) in overseeing the successful implementation of the accounting procedures. This type of research is descriptive, analysis instruments used are the Internal Control Quisionare (ICQ) using a Likert scale, document analysis and identification. The results of this research showed the success rate of procedures implementation of accounting base of accrual by Regional Work Unit of urban comunities (SKPD Kelurahan) about 71.48% which is good interpretation either by need a little improvement, by Head of local government financial management office (PPKD) about 81.98% which is very good interpretation. The Inspectorate of Ketapang Regency success rate in supervice procedures of Accounting Base of Accrual about 59.11% with a pretty good interpretation either by need much improvement. The difference due to the success rate caused by fully accrual accounting procedures in the preparation of Financial Reports has not been implemented both on the accounting entity and the reporting entity, also surveillance for the implementation of accounting procedures in the preparation of Financial Reports by the Inspectorate of Ketapang Regency was not yet carried out. The quality of reports produced about 74.00% which is good interpretation either by need a little improvement. The Regional Work Unit of Urban Communities (SKPD kelurahan) success rate is not directly impact to the Head of local government financial management office (PPKD) success rate. The Both success does not impact directly to the successfull supervision by the Inspectorate of Ketapang Regency. Such a condition needed enhacement / improvement in the implementation of accounting procedures by the both accounting entity and the reporting entity, PKPT Preparation, stages and goal surveillance implementation. enhacement / improvement is expected to accelerate the implementation of accrual based accounting system in the preparation of Financial Reports and improve the quality of reports produced and increase surveillance success. Keyword : Implementation of accounting procedure, Finacial Report and Quality of Financial Report.